2002
DOI: 10.1136/gut.51.5.723
|View full text |Cite
|
Sign up to set email alerts
|

Mild iron overload in patients carrying the HFE S65C gene mutation: a retrospective study in patients with suspected iron overload and healthy controls

Abstract: Background and aims: The role of the HFE S65C mutation in the development of hepatic iron overload is unknown. The aim of the present study was: (A) to determine the HFE S65C frequency in a Northern European population; and (B) to evaluate whether the presence of the HFE S65C mutation would result in a significant hepatic iron overload. Patients and methods: Biochemical iron parameters and HFE mutation analysis (for the C282Y, H63D, and S65C mutations) were analysed in 250 healthy control subjects and collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 22 publications
1
42
0
2
Order By: Relevance
“…Similar to C282Y heterozygosity, a very mild effect of S65C mutation on iron overload has also been noted. 91 The associations described later are most likely the result of serum iron elevation in heterozygotes.…”
Section: Diseasementioning
confidence: 94%
“…Similar to C282Y heterozygosity, a very mild effect of S65C mutation on iron overload has also been noted. 91 The associations described later are most likely the result of serum iron elevation in heterozygotes.…”
Section: Diseasementioning
confidence: 94%
“…9 We consider these data relevant and meritorious for further investigation due to the importance of this mutation in iron overload according to the literature. [18][19][20] Bittencourt et al 21 analyzed the HFE gene in 15 HH patients and found 53% of C282Y homozygous and 7% of heterozygous individuals. None had the compound heterozygous C282Y/H63D.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were excluded because some or all of their participants’ genotypes were reported in other studies included in the analysis [18, 19]. Furthermore, studies using only healthy controls or including non-Caucasians were excluded, as they would tend to underestimate HFE mutation frequencies [5, 9, 11, 20, 21, 22, 23, 24, 25]. Expected genotype and allele frequencies for C282Y and H63D were calculated from data including 38,658 alleles from the nine studies indicated in table 2 [6, 7, 10, 12, 13, 14, 15, 16, 17].…”
Section: Methodsmentioning
confidence: 99%
“…Many publications have examined the prevalence and role of C282Y and H63D in the development of HH. However, only a few recent studies have included the S65C mutation, and all of them include a selection bias [5, 6, 7, 8, 9, 10, 11]. In this study, we report the prevalence of the C282Y, H63D and S65C alleles in an unselected Michigan non-Hispanic Caucasian population and assess any significant deviation of these frequencies from the expected population frequencies based on previous reports.…”
Section: Introductionmentioning
confidence: 99%